Prediction of petrophysical characteristics of deposits in Kurovdagh field by use of attribute analysis of 3D data - Akhmedov, T.R.; Aghayeva, M.A. (Geofizicheskiy Zhurnal, 2022)
The paper is devoted to predicting petrophysical parameters of productive series of Kurovdagh field by use of attribute analysis of seismic data to define the direction of reconnaissance works in this field. The paper considers geographical position of the study area, its cover by geological and geophysical studies and underlines, in particular, the importance of 3D seismic data acquisition for more detailed study of Kurovdagh structure. Lithological and stratigraphic characteristics of the section is also given in the paper with detailed description of Productive Series deposits. In addition, tectonics of the area is considered in more detail. It is noted that the area is attributed to the Low Kur basin — the compound of the large tectonic unit. The tectonic zone of the south-eastern Shirvan is embracing four anticlinal zones: Pirsaat-Khamamdagh; Kharami—Mishovdag—Kalmas—Khydirly—Aghaevir-Byandovan; Kursangya; Padar—Kurovdagh—Karabaghly—Babazanan—Duzdagh-Neftchala. The latter anticlinal zone is characterized by a significant length. In the north-western part between the folds of Padar and Karabaghly the brachyanticline of Kurovdagh is located. In the north it has the border with M. Kharami uplift, in the north-east with Mishovdagh fold, it borders with Kursyanga anticline in the south-east and in the south-west with wide Salyan trough. In the Near-Kur depression the existence of two tectonic stripes has been established. One of them embraces the south-eastern Shirvan, the other covers the eastern Mughan and the western portion of Salyan steppe. The detailed description of fold setting is given on the basis of 3D seismic survey data. It has been indicated that the results of 3D data interpretation made it possible to study in more detail and make changes in the scheme of faults location accepted earlier. The other problem considered in the paper is the oil-and-gas presence in Kurovdagh field, which is related to the Absheron stage of Pleistocene, Akchagyl stage and Productive series (horizons of PS01—PS20) of Neogene, with lithology represented by sandy-clay rocks with various degrees of calcareousness. The structure of each of indicated horizons is rather complicated and variable in lateral. The most complicated of them is the Middle Absheron sub-stage, with identified 11 oil-bearing layers. Study results are given in the end of the paper. For prediction purposes within the study area we have prepared normalized curves of relative parameter of SP-ASP, gamma-log — dGR and resistivity by use of well logging data. The analysis of dependence of seismic attributes on petrophysical parameters within target interval, identified the low information bearing ability of SP method and gamma-log across the study area and established a good correlation between resistivity curve and instantaneous amplitudes, frequencies and dip angles. The clay cubes have been designed. To outline productive layers, we have applied multidimensional filters with cut offs for reservoir and as a result we have acquired a cube for supposed distribution of productive layers. It is emphasized that the conducted studies led to the conclusion that due to the complexity and interference nature of the observed wave pattern in some parts of the Kurovdagh structure, it was not possible to reliably convert the attributes of the seismic wave field into petrophysical parameters.